Case Report: Vision Training for National Hockey League Goaltender, Rogatien Vachon - Dalziel, Carol C. (Canadian Journal of Optometry, 1982)
This non-strabismic patient had an insignificant refractive error, a small esophoria, low fusional vergences, no fixation disparity and symptoms related to and interfering with his goaltending. Compared to his right eye, his left demonstrated slower motor responses, unsteady fixation and a tendency to overshoot with version, vergence and reading tasks on an Eye Trac instrument. A vision training program was designed to encourage faster and more accurate symmetrical and asymmetrical vergence changes, version and tracking eye movements, and accommodative facility. After three months of daily exercises, binocular coordination and goaltending performance had improved and symptoms were relieved.